Night‐time gastric acid suppression by tegoprazan compared to vonoprazan or esomeprazole. Issue 7 (23rd February 2022) - Yang, Eunsol; Kim, Seokuee; Kim, Bongtae; Kim, Boram; Kim, Yechan; Park, Sung Sup; Song, Geun Seog; Yu, Kyung‐Sang; Jang, In‐Jin; Lee, SeungHwan
Abstract : Aims: Nocturnal acid breakthrough has been considered an unmet need of proton‐pump inhibitors. Tegoprazan, a novel potassium‐competitive acid blocker, is expected to show improved properties for this unmet need. This study was aimed to compare night‐time acid suppression by tegoprazan with that by vonoprazan or esomeprazole, and to explore the effect of CYP2C19 phenotypes on acid‐suppressive effects. Methods: A randomized, open‐label, 3‐period, 6‐sequence crossover study was conducted. A single oral dose of tegoprazan 50 mg, vonoprazan 20 mg or esomeprazole 40 mg was administered at night in each period. Continuous intragastric pH was monitored at baseline and after each dosing. Results: Sixteen healthy subjects (6 CYP2C19 extensive metabolizers, 5 intermediate metabolizers, 5 poor metabolizers) completed the study. After a single dose of tegoprazan, intragastric pH increased more rapidly to over 4 at approximately 1 hour compared to the other treatments, and elevated intragastric pH was maintained stably at night. Tegoprazan exhibited night‐time acid suppression for slightly but not significantly longer than vonoprazan, and greater than esomeprazole; % time at pH ≥ 4 at night was 66.0%, 60.5% and 36.1% for tegoprazan, vonoprazan and esomeprazole, respectively. Night‐time acid suppression by tegoprazan and vonoprazan was not dependent on CYP2C19 phenotypes, while that by esomeprazole tended to be influenced by CYP2C19 phenotypes. Conclusion: Tegoprazan produced more rapid, potent and well sustained night‐time acid suppression vs . vonoprazan or esomeprazole when administered at night. Furthermore, tegoprazan showed no CYP2C19 phenotype dependency in acid suppression. It suggests the potential of tegoprazan, especially in preventing nocturnal acid breakthrough.